"That's enough patients for everyone!": Local stakeholders' views on attracting patients into Barbados and Guatemala's emerging medical tourism sectors. Issue 1 (December 2016) - Snyder, Jeremy; Crooks, Valorie; Johnston, Rory; Cerón, Alejandro; Labonte, Ronald
Abstract Background Medical tourism has attracted considerable interest within the Latin American and Caribbean (LAC) region. Governments in the region tout the economic potential of treating foreign patients while several new private hospitals primarily target international patients. This analysis explores the perspectives of a range of medical tourism sector stakeholders in two LAC countries, Guatemala and Barbados, which are beginning to develop their medical tourism sectors. These perspectives provide insights into how beliefs about international patients are shaping the expanding regional interest in medical tourism. Methods Structured around the comparative case study methodology, semi-structured interviews were conducted with 50 medical tourism stakeholders in each of Guatemala and Barbados (n = 100). To capture a comprehensive range of perspectives, stakeholders were recruited to represent civil society (n = 5/country), health human resources (n = 15/country), public health care and tourism sectors (n = 15/country), and private health care and tourism sectors (n = 15/country). Interviews were transcribed verbatim, coded using a collaborative process of scheme development, and analyzed thematically following an iterative process of data review. Results Many Guatemalan stakeholders identified the Guatemalan-American diaspora as a significant source of existing international patients. Similarly, Barbadian participants identified their large recreational tourism sector as creating a ready source of foreign patients with existing ties to the country. While both Barbadian and Guatemalan medical tourism proponents share a common understanding that intra-regional patients are an existing supply of international patients that should be further developed, the dominant perception driving interest in medical tourism is the proximity of the American health care market. In the short term, this supplies a vision of a large number of Americans lacking adequate health insurance willing to travel for care, while in the long term, the Affordable Care Act is seen to be an enormous potential driver of future medical tourism as it is believed that private insurers will seek to control costs by outsourcing care to providers abroad. Conclusions Each country has some comparative advantage in medical tourism. Assumptions about a large North American patient base, however, are not supported by reliable evidence. Pursuing this market could incur costs borne by patients in their public health systems.